New Imaging Methods for Non-invasive Assessment of Mechanical, Structural, and Biochemical Properties of Human Achilles Tendon: A Mini Review - Fouré, Alexandre (Frontiers in Physiology, 2016)
The mechanical properties of tendon play a fundamental role to passively transmit forces from muscle to bone, withstand sudden stretches and act as a mechanical buffer allowing the muscle to work more efficiently. The use of non-invasive imaging methods for the assessment of human tendon’s mechanical, structural and biochemical properties in vivo is relatively young in sports medicine, clinical practice and basic science. Non-invasive assessment of the tendon properties may enhance the diagnosis of tendon injury and the characterization of recovery treatments. While ultrasonographic imaging is the most popular tool to assess the tendon’s structural and, indirectly, mechanical properties, ultrasonographic elastography and ultra-high field magnetic resonance imaging (UHF MRI) have recently emerged as potentially powerful techniques to explore tendon tissues. This paper highlights some methodological cautions associated with conventional ultrasonography and perspectives for in vivo human Achilles tendon assessment using ultrasonographic elastography and UHF MRI.